2014
DOI: 10.4238/2014.july.2.7
|View full text |Cite
|
Sign up to set email alerts
|

New roles of filopodia and podosomes in the differentiation and fusion process of osteoclasts

Abstract: ABSTRACT. The cytoskeleton mediates various cellular processes such as differentiation and fusion, including in the filopodia and podosomes. However, apart from cell migration and formation of the sealing zone, little is known regarding the changes and related regulatory mechanisms of the cytoskeleton and additional roles of the filopodia and podosomes during the differentiation and fusion of osteoclasts. The cytomorphology and cytoskeleton of osteoclasts in the differentiation process were evaluated using tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 36 publications
2
27
0
1
Order By: Relevance
“…A number of studies have also confirmed that RhoGTPases control F-actin polymerization and adhesion, and play an important role in the formation of the sealing zone in osteoclasts (29)(30)(31)(32)(33). As shown by our previous study (34) and a study by other researchers (18), RhoH, RhoJ/TCL and RhoE/Rnd3 are not expressed during osteoclast differentiation and maturation. In addition, the expression of RhoQ/TC10, RhoV/Chp1 and RhoBTB2 is markedly inhibited during the formation of osteoclasts.…”
Section: Discussionsupporting
confidence: 55%
“…A number of studies have also confirmed that RhoGTPases control F-actin polymerization and adhesion, and play an important role in the formation of the sealing zone in osteoclasts (29)(30)(31)(32)(33). As shown by our previous study (34) and a study by other researchers (18), RhoH, RhoJ/TCL and RhoE/Rnd3 are not expressed during osteoclast differentiation and maturation. In addition, the expression of RhoQ/TC10, RhoV/Chp1 and RhoBTB2 is markedly inhibited during the formation of osteoclasts.…”
Section: Discussionsupporting
confidence: 55%
“…Invadosomes have been described in a variety of normal cell types, including osteoclasts [80], macrophages [79], endothelial cells [81] and neurons [82] in normal physiological contexts, and in tumor cells [79]. The term “invadosome” also includes macrophage podosomes and tumor cell invadopodia but these have well-documented differences in structure, molecular pathways, and functions.…”
Section: Invadopodia In Cancermentioning
confidence: 99%
“…There is increasing evidence that activation of Rac1 and/or Rac2 in osteoclasts may play an essential role in osteoclast fusion . Rac1/Rac2 activation (through PTP‐oc‐dependent β 3 ‐integrin‐mediated activation of Vav3) is a key downstream component of the PTP‐oc/EphA4 pathway in osteoclasts .…”
Section: Discussionmentioning
confidence: 99%